2010
DOI: 10.7886/hgs.85.26
|View full text |Cite
|
Sign up to set email alerts
|

Wolf Depredation on Livestock in the Pamir

Abstract: The questionnaire survey shows that 94.4% of the respondents consider reducing the wolf population a necessity.The existing measures against wolf depredation on livestock do not function well, so they need to be improved and strengthened.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 10 publications
0
8
1
Order By: Relevance
“…Studies carried out on human–wildlife conflicts concluded that wildlife-affected people hold negative feelings for carnivores [62,63,64,65]. In our study the interviewees shared a negative attitude towards the wolf and desired to reduce or eliminate it from their area.…”
Section: Discussionmentioning
confidence: 70%
“…Studies carried out on human–wildlife conflicts concluded that wildlife-affected people hold negative feelings for carnivores [62,63,64,65]. In our study the interviewees shared a negative attitude towards the wolf and desired to reduce or eliminate it from their area.…”
Section: Discussionmentioning
confidence: 70%
“…Wolves were responsible for the majority of livestock losses in the Tajik (100%) and Afghan (70%) Pamirs, while the snow leopard was found to be the major predator in the Pakistani Pamirs (65%). Wolf predation has been a major issue in the Pamirs (Izumiyama et al 2009) and has been controlled lethally by the locals by paying hunters to kill them (Watanabe et al 2010).…”
Section: Discussionmentioning
confidence: 99%
“…Available literature (Hussain 2000, Mishra and Fitzherbert 2004, Watanabe et al 2010) describes mass killing of both snow leopards and wolves in the Pamirs. The majority of respondents perceived wolves and snow leopards as lethal for livestock and consequently expressed desires to see reduced populations.…”
Section: Discussionmentioning
confidence: 99%
“…and woolly monkeys (Lagothrix sp.) in the Amazon basin (Kumpel et al, 2010), and the wolf populations of the Pamir region of Kyrgyzstan and Tajikistan (Watanabe et al, 2010). Loss of biological diversity within already established protected areas indicates a distinct institutional/administrative weakness, especially when they have governmental support, legal protection and formal governing organization (Oestreicher et al, 2009).…”
Section: Parks Vol 201 March 2014mentioning
confidence: 99%
“…On the contrary, the 2-3 tigers killed each year in and around the Sundarbans due to attacks on human or livestock, plus an unknown number poached, could threaten the longterm viability of the tiger population (which is estimated at about 150 adult females). Controlling 'problem animals' due to human-wildlife conflict is a global issue, and includes conflicts with Amur Tiger (Panthera tigris altaica) in the Far East provinces of Russia (Goodrich et al, 2011), wolves in the Pamir regions of Kyrgyzstan and Tajikistan (Izumiyama et al, 2009;Watanabe et al, 2010), lions in Masai region of Kenya and Tanzania (Okello & Hadas, 2000). Tiger conservation in Bangladesh must take into account the local socioeconomic conditions of which human-tiger conflict is an important feature (Barlow, 2009).…”
Section: Parks Vol 201 March 2014mentioning
confidence: 99%